Thoracic Radiography Findings of Multi Drug Resistant Tuberculosis at Dr. Hasan Sadikin General Hospital Bandung - Mareta Tada Kurnia; Iyus Maolana Yusuf; Prayudi Santoso (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: The prevalence of multidrug-resistant pulmonary tuberculosis (MDR-TB) continues to increase, especially in Indonesia. Thoracic radiography examination plays a role in the TB diagnosis by providing findings of typical lesions in patients. The aim of the study was to determine the thoracic radiography findings in MDR-TB patients.Methods: This was a cross-sectional retrospective descriptive study. This study had explored secondary data from medical records of patients who previously had a clinical diagnosis of MDR-TB and underwent thoracic radiography examinations at the Department of Radiology, Dr. Hasan Sadikin General Hospital, Bandung on July - August 2020 Result: Of 110 data collected, the average age was 37±12.6 years with male patients were predominantly prevalent and 65.5% had large lesions. The most frequent findings of lesions were calcification (94.5%) and fibrosis (90.9%). Other major findings were infiltration (88.2%), consolidation (55.5%), cavity (65.5%), ground-glass opacity (60.9%) while other were found in less than half of the cases such as bronchiectasis (23%), nodule (34.5%), atelectasis (36.4%), lymphadenopathy (34.5%), and others. Interestingly, the miliary pattern was not found.Conclusion: Large lesions, calcification, fibrosis, infiltration, consolidation, cavities, and ground-glass opacities are the main features of the radiographic findings in the majority of MDR-TB patients.